Daphnis Et Chloé: suite No. 2 - Ravel, Maurice. 1875-1937 (Dover Miniature Scores, 1999)
This 20th-century orchestral masterpiece offers a rich musical setting of a pastoral Greek fable by Longus. Commissioned by Diaghilev for the Ballet Russes, the work premiered in Paris in 1912.